The Problem of Artificial Intelligence and Intellectual Property Rights - Faizullayeva Iqboloy Ghairatovna (Scientific Trends, 2025)
This article is based on the fact that the development of information technologies, nanotechnologies, biotechnology, cognitive technologies, automation and rabotization of production, digitization and robotizatsion of production, digitizatsion and cybernetcization of management are placing new professional and requirements on the trends in the dynamics of demand for professions, the decrease in demand for some popular proffessions, and the increase in demand for some new professions.
Keywords: Intelligence, artificial intelligence, natural intelligence, modern technologies, nanotechnology, smart technologies, competition, unemployment, copyright, plagiarism.